Contemporary Management of Secondary Mitral Regurgitation - Kashish Goel; Colin M Barker; JoAnn Lindenfeld (European Cardiology Review)
Secondary mitral regurgitation (SMR) is a common occurrence in patients with heart failure with reduced ejection fraction. Moderate-severe or severe SMR is associated with increased mortality and hospitalisations from heart failure. Medical and cardiac resynchronisation therapies have been the only treatments proven to improve prognosis in this patient population. The Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy (COAPT) and the Percutaneous Repair with the MitraClip Device for Severe Functional/Secondary Mitral Regurgitation (MITRA-FR) RCTs evaluated transcatheter mitral valve repair with MitraClip for treatment of SMR in addition to medical therapy and they had divergent results. The COAPT trial demonstrated that a reduction in SMR with MitraClip resulted in reduced mortality and heart failure hospitalisations along with improved symptoms and quality of life in appropriately selected patients. The MITRA-FR trial did not show any benefit from using MitraClip for patients with SMR. This article summarises the differences in these two trials and suggests a contemporary approach to the management of SMR.